Is there benefit to concurrent x‐ray imaging of the wrist, forearm and elbow in paediatric patients following a fall on the outstretched hand?. Issue 4 (16th August 2022) - Sgualdino, Daniel G; Neep, Michael J; Spuur, Kelly; Hughes, Clarissa
Abstract: Introduction: Concurrent X‐ray imaging of the wrist, forearm and elbow in paediatric patients following a fall on the outstretched hand (FOOSH) is intended to minimise the risk of an undetected co‐occurring injury and is typically performed on patients aged 0–10 years. The purpose of this study was to explore the benefit of this strategy and to identify if age could provide evidence for imaging. Methods: A 12‐month retrospective review of all X‐ray examinations of the wrist, forearm and distal humerus of patients aged 0–10 years referred from the Emergency Department of Logan Hospital, Queensland was undertaken. The frequency, type and location of radiographic abnormalities and the requested examinations region of interest (ROI), referral notation and patient's age were recorded. Analysis was made by descriptive statistics. Results: Four hundred and seventy‐six examinations met the studies inclusion criteria, 4.8% ( n = 23) identified an abnormality outside of the documented ROI. On review of the admission and treatment notes, 1.7% ( n = 8) were deemed to have detected traumatic abnormalities as a direct outcome of concurrent imaging. No age‐related evidence for imaging was identified. Conclusion: This study demonstrates limited benefit (1.7%) to concurrent imaging following a FOOSH. The results suggest that a thorough physical evaluation of the paediatric upper limb performed by the referrer is sufficient to accurately guide X‐ray imaging. These findings have the potential to positively impact a reduction in the number of X‐rays performed on paediatric patients and in turn contribute to limiting radiation dose. Further studies may be beneficial in verifying the study's findings. Abstract : There is a limited benefit (1.7%), of concurrent imaging of the wrist, elbow and forearm in paediatric patients following a FOOSH where there is no clinical indication for imaging outside of the region of interest. Results support previous findings that a thorough clinical assessment of the wrist, forearm and elbow is sufficient to guide X‐ray imaging.